Hubungan Jarak Tempuh Dan Efek Samping Terhadap Kepatuhan Kemoterapi Pada Pasien Kanker Serviks - Elya Rikke Fitriana; Ns. Anis Ardiyanti; Nella Vallen Ika Puspita (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Cervical cancer is a deadly cancer for women but some medication could be applied, such as chemotherapy. Chemotherapy has some side effects on these patients if they do not obey. This research determined the correlation between the distance coverage and the side effects on the obedience of cervical cancer patients with chemotherapy at DR. Moewardi Surakarta regional hospital. This quantitative research applied a cross-sectional design. The population consisted of 102 cervical cancer patients with chemotherapy. The researchers took the sample with purposive sampling. The samples were 49 patients measured with the questionnaire of chemotherapy obedience and chemotherapy side effect; and the observational guideline of distance coverage. The results showed that most respondents had a far category distance, 45 respondents (91.8%) and maladaptive side effect type, 37 respondents (75.5%). The Spearman rank test showed the correlation between the distance coverage and the obedience with a p-value of 0.004, lower than 0.05. The result also showed the correlation between side effects and obedience with a p-value of 0.044, lower than 0.05. The results found a correlation between the distance coverage and side effects toward the obedience of cervical cancer chemotherapy.